2013
DOI: 10.2340/16501977214553
|View full text |Cite
|
Sign up to set email alerts
|

Isometric and isokinetic knee extension and flexion torque in men and women aged 20-70

Abstract: An investigation was made of the influence of age and sex on peak muscle torque in knee extension and flexion during maximal isokinetic and isometric contraction. The study was performed on both legs of 139 clinically healthy men and 141 clinically healthy women aged 20, 30, 40, 50, 60 or 70 years. Maximum knee extension and flexion muscle torque (Newtonmetre, Nm) was measured isokinetically at various angles of velocity (12, 90 and 150 degrees/s) and isometrically under standardized conditions (Cybex II). No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Sjo ¨lander et al [22] showed that peripheral sensory inputs from ligament afferents participate in continuous control of muscle activity through feed-forward, or preprogramming, mechanisms. Moreover, poor neuromuscular control with weak ligament muscular reflexes and no muscular stretch reflexes is indicative of the ineffectiveness of the acute muscular reaction in providing early mechanical knee stabilization after injury [7]. It has also been suggested that ligament mechanoreceptors play an important role in muscle coordination and reflex regulation of functional joint stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sjo ¨lander et al [22] showed that peripheral sensory inputs from ligament afferents participate in continuous control of muscle activity through feed-forward, or preprogramming, mechanisms. Moreover, poor neuromuscular control with weak ligament muscular reflexes and no muscular stretch reflexes is indicative of the ineffectiveness of the acute muscular reaction in providing early mechanical knee stabilization after injury [7]. It has also been suggested that ligament mechanoreceptors play an important role in muscle coordination and reflex regulation of functional joint stability.…”
Section: Discussionmentioning
confidence: 99%
“…As the healthy leg was the left leg in all subjects, the effect of ACL deficiency on knee extension and flexion may have been attenuated by decreased torque in the healthy leg. Borges [7] reported no significant differences in knee extension and flexion torques between the right and the left legs of healthy women and men aged 20–70 years.…”
Section: Discussionmentioning
confidence: 99%
“…Ghena et al [6] tested subjects at speeds up to 500°/sec. For the knee joint, velocities above 180°/sec are defined as high velocities [6,21]. The gain increase at high angular velocities and whether it provides meaningful data is controversial.…”
Section: Isokinetic Strength Measurementmentioning
confidence: 99%
“…The first step of the diagnosis level is based on altered skeletal muscle functional parameters considering strength. Patients with less than 80% of the predicted quadriceps peak torque as assessed by using a computerized dynamometer (Biodex System 4 Pro) were classified as presenting altered skeletal muscle function [21]. The next step, which is based on altered body composition, was confirmed in patients with increased FM and reduced muscle mass.…”
Section: Anthropometric and Body Composition Measurementsmentioning
confidence: 99%
“…Endurance exercise capacity was measured by a submaximal constant work-rate cycle test (CWRT) at 75% of the pre-identified W max [28]. Isokinetic quadriceps muscle function was determined using a Biodex System 4 Pro (Biodex Medical Systems, Inc., NY, USA) [21]. Quadriceps muscle strength was defined as the highest peak torque (Nm), whereas isokinetic quadriceps muscle endurance was be defined as the total amount of delivered work (Joules) during a set of 30 repetitions.…”
Section: Other Assessmentsmentioning
confidence: 99%